1995
DOI: 10.1164/ajrccm.151.6.7767536
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of exhaled nitric oxide in bronchiectasis.

Abstract: Bronchiectasis is characterized by chronic inflammation in one or more bronchi, but the extent of inflammation is difficult to monitor. The concentration of nitric oxide (NO) in exhaled air is increased in asthmatic patients, possibly as a result of the chronic inflammatory process. We have measured exhaled NO in patients with documented bronchiectasis and investigated whether the concentration of exhaled NO is related to the extent of disease as defined by computed tomography (CT) and lung function. In 20 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
153
4
3

Year Published

1997
1997
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(161 citation statements)
references
References 23 publications
1
153
4
3
Order By: Relevance
“…Exhaled NO has been demonstrated to be elevated in airway inflammatory diseases, suci asthma and bronchiectasis (Kharitonov et al, 1995(Kharitonov et al, 1996, but the precise cellular source of exhaled N In the present study, we have provided direct evider ence and distribution of NOS in lung tissues and f production of nitrite from AM in patients with cancer. The iNOS expression of AM was up-regul with primary lung cancer compared with that subjects.…”
Section: Discussionmentioning
confidence: 53%
“…Exhaled NO has been demonstrated to be elevated in airway inflammatory diseases, suci asthma and bronchiectasis (Kharitonov et al, 1995(Kharitonov et al, 1996, but the precise cellular source of exhaled N In the present study, we have provided direct evider ence and distribution of NOS in lung tissues and f production of nitrite from AM in patients with cancer. The iNOS expression of AM was up-regul with primary lung cancer compared with that subjects.…”
Section: Discussionmentioning
confidence: 53%
“…The exhaled NO concentration is increased in airway inflammation 12,36,37 and is suppressed in substances may interact with NO is not presently known.…”
Section: Discussionmentioning
confidence: 97%
“…This regulatory pathway balancing inflammation and NO production is relevant to pulmonary disorders such as diffuse panbronchiolitis, CF, and ciliary dyskinesia, which are thought to involve NO dysregulation in the presence of excessive inflammation (7,13,21,22,24). It has been previously reported that exhaled NO is depressed in patients with these disorders, in contrast to other inflammatory lung disorders such as asthma, bronchiectasis, and chronic bronchitis (3,7,14,15,21,24), which may be partially due to reduced NOS2 expression in CF airway epithelial cells (13,22). Because NO also acts as an anti-inflammatory, it is suggested that this lack of NO in CF airways contributes to the hyperinflammatory response to chronic bacterial infection characteristic of this disease (13,22).…”
Section: Discussionmentioning
confidence: 99%